Validity and reliability of Turkish transcultural adaptation of the Prosthetic Limb Users Survey of Mobility. Issue 2 (25th April 2023) - Yosmaoglu, Sevgin; Yazicioglu, Gul; Demir, Yasin; Aydemir, Koray; Yosmaoğlu, Hayri Baran
Abstract : Background: Amputee-specific, self-assessment mobility scales are essential to evaluate mobility in lower-limb amputees. Objectives: To evaluate the validity and reliability of a Turkish translation and adaptation of the Prosthetic Limb Users Survey of Mobility. Study design: This is a validation study. Methods: Turkish translation of the Prosthetic Limb Users Survey of Mobility (PLUS-M-T) from its original was performed following the rules of intercultural adaptation and translation methods. The PLUS-M-T and its 12-item short form were applied to '100 induviduals with limb loss twice in 3-day intervals. The structural validity analysis was determined by calculating the correlation with the Amputee Mobility Scale, which is a valid, reliable scale for assessing the functional level in amputees. The Cronbach alpha coefficient was calculated to analyze the internal consistency. The interclass correlation coefficient (ICC) and Spearman correlation coefficient (r) were calculated, and the test–retest reliability was determined. Results: A positive, high correlation was found between the first application and its repetition of both PLUS-M-T (ICC = 0.85, r = 0.94, P < 0.001) and 12-item short form (ICC = 0.92, r = 0.93, P < 0.001). The internal consistency was high for both PLUS-M-T (Cronbach alpha = 0.94) and 12-item short form (Cronbach alpha = 0.91). A positive, high correlation was found between the scores obtained from the Amputee Mobility Scale and PLUS-M-T (r = 0.84, P < 0.001) and 12 question short form (r = 0.77, P < 0.001). Conclusion: Turkish translation of the PLUS-M questionnaire is a valid and reliable scale for assessing the mobility of individuals who have undergone lower-extremity amputation using a prosthesis.